Successful treatment of acrodermatitis continua of Hallopeau coexisting with generalized pustular psoriasis with spesolimab: a case report - Wen, Pengfei; Liu, Chuan; Wang, Tingting; Jiang, Xian; Wang, Ping; Wang, Sheng (Frontiers in Immunology, 2024)
Generalized pustular psoriasis（GPP）is a rare chronic inflammatory pustular dermatosis that presents as painful erythema with sterile pustules on nonacral skin. No unified standard and guideline for the treatment of GPP has been established. Several biologics have been tried for GPP, with varying success. Acrodermatitis continua of Hallopeau (ACH) is a very rare disabling variant of pustular psoriasis characterized by sterile pustules on the fingers and toes, including the nail bed. Comparatively, treating ACH is highly challenging due to its commonly therapy-resistant disease course. The pathogenic role of IL-36 signaling axis has been currently identified in GPP development. Spesolimab, the first anti-interleukin-36 receptor biologic, has been approved for treating GPP flares and shown promising results. In view of a shared pathogenesis between GPP and ACH, specolimab may be an effective treatment for ACH. Currently, there is no case and clinical trial data exist on this condition. Therefore, this case was aim to describe real-world experience of spesolimab use in ACH coexisting with GPP. We report an Asian patient with a 16-year-history of GPP and ACH with marked pustulosis on the nail bed and onychodystrophy. He received conventional systemic regimen acitretin, cyclosporine and biologics adalimumab and secukinumab, but experienced relapse for skin lesions and refractory for nail lesions. He was then treated with a single dose of spesolimab in combination with secukinumab, which resulted in skin clearance and nearly complete resolution of nail lesions over a 32-week period. Our observation suggests that spesolimab should be considered for the treatment of ACH, especially in the patients with intractable nail lesions and concomitant GPP.